Constitution of the Identity Teaching Professional - Silva, Antonia Zulmira (2022)
The present paper shows a cutout of the research that investigates the processes of identity of Elementary School teachers of São Paulo state public school network. The development of the research promoted a discussion on the constitution of teaching professional identity, along with a theoretical framework on the topic. Therefore, the purpose of the present paper is to present the teachers’ perceptions regarding teaching and to understand how the process of constitution of professional identity occurs, based on the teachers’ statements and theoretical frameworks. The investigation has a qualitative approach; as the main procedure of the investigation, questionnaires and interviews were conducted with the research subjects, the teachers. For theoretical analysis, the method of content analysis was developed. From the analyses of collected data, we may infer that teaching identity develops through a lively and evolving process that can be influenced by internal and external factors, as well as by the relationships in professional context, which can be long or short depending on the circumstances of different moments and contexts.